2019
DOI: 10.1109/jlt.2018.2886047
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Effects on Modal Properties of Dual-Core Yb-Doped Fibers

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…The characteristics of the Yb-doped 4-core fibers studied in this analysis are analogous to the ones of the dual-core fibers considered in [16]. In particular, for each core the diameter is fixed to 19 µm and the refractive index is properly modified to obtain the V -parameter equal to 1.735, 2.2 and 2.4, while keeping fixed the silica refractive index for the cladding, thus providing an intrinsically single-mode behaviour at the signal wavelength of 1032 nm.…”
Section: Yb-doped 4-core Fibersmentioning
confidence: 86%
See 2 more Smart Citations
“…The characteristics of the Yb-doped 4-core fibers studied in this analysis are analogous to the ones of the dual-core fibers considered in [16]. In particular, for each core the diameter is fixed to 19 µm and the refractive index is properly modified to obtain the V -parameter equal to 1.735, 2.2 and 2.4, while keeping fixed the silica refractive index for the cladding, thus providing an intrinsically single-mode behaviour at the signal wavelength of 1032 nm.…”
Section: Yb-doped 4-core Fibersmentioning
confidence: 86%
“…1(left), the four Yb-doped cores are placed at the vertices of a square of side d, varied in the range between 20 µm and 65 µm. The outer part of the 4-core fiber cross-section is the same described in [16]. In particular, we consider an outer diameter sufficiently large to render the fiber unbendable, a so-called rod-type fiber.…”
Section: Yb-doped 4-core Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…The scalar mode fields m have been estimated as the dominant polarization components of full-vectorial solutions obtained with a commercial full-vector modal solver based on the finite element method [15,17,18], with subsequent renormalization according to Eq. (7).…”
Section: B Numerical Methodsmentioning
confidence: 99%
“…We neglect thermo-optic modifications to the transverse mode profiles, which may have some impact on the quantitative results, leading to an overestimate of the intercore coupling. However, a recent finite-element study indicated that the mode profiles in the structure considered were not strongly modified at thermal loads of a few tens of W/m [15], which is the regime we are considering in most of the simulations.…”
Section: Formal Theory a Coupled-mode Formalismmentioning
confidence: 95%